SOCIFS feature selection framework for handwritten authorship - Draman @ Muda, Azah Kamilah; Choo, Yun Huoy; Draman @ Muda, Noor Azilah (IOS Press, 2013)
The uniqueness of shape and style of handwriting can be used to identify the significant features in confirming the author of writing. This paper is meant to propose a novel feature selection framework for Swarm Optimized and Computationally Inexpensive Floating Selection (SOCIFS), by exploring existing feature selection frameworks, and compare the performance of proposed feature selection framework against various feature selection methods in Writer Identification in order to find the most significant features. The promising applicability of the proposed framework has been demonstrated in the result and worth to receive further exploration in identifying the handwritten authorship.